2011
DOI: 10.1002/pssb.201046614
|View full text |Cite
|
Sign up to set email alerts
|

Scanning thermal microscopy: A nanoprobe technique for studying the thermal properties of nanocomponents

Abstract: In this paper, a novel micromachined scanning thermal microscopy (SThM) microcantilever with a sharp, conductive platinum tip is proposed for temperature and thermal conductivity measurements in sub-micron structures of micro- and nanoelectronic components. The idea and physical background of SThM operation is presented, together with brief description of probes and example images of a planar polycrystalline-silicon microfuse obtained using passive- and active-mode SThM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…200 A number of developments based on new cantilevers and new AFM-based temperature measuring techniques have been stated in recent years. 43,45,[201][202][203][204][205][206][207][208][209][210] Sadat et al 23 have reported a thermometric AFM-based technique which does not require integrated temperature sensors in AFM probes. The technique allows direct mapping of topography and temperature fields of metal surfaces with $0.01 degree temperature resolution and <100 nm spatial resolution.…”
Section: Scanning Thermal Microscopymentioning
confidence: 99%
“…200 A number of developments based on new cantilevers and new AFM-based temperature measuring techniques have been stated in recent years. 43,45,[201][202][203][204][205][206][207][208][209][210] Sadat et al 23 have reported a thermometric AFM-based technique which does not require integrated temperature sensors in AFM probes. The technique allows direct mapping of topography and temperature fields of metal surfaces with $0.01 degree temperature resolution and <100 nm spatial resolution.…”
Section: Scanning Thermal Microscopymentioning
confidence: 99%
“…However, the amplitude of this component is much less than of the lower harmonics, which means that a use of a precise lock-in amplifier (capable of processing the third harmonics), preceded by a preamplifier in the SThM module, is necessary (Lefèvre & Volz, 2005;Chirtoc & Henry, 2008;Wielgoszewski et al, 2011a). The 3ω-SThM is useful as a method of mapping the temperature and thermal conductivity (Altes, Heiderhoff, & Balk, 2002), but also for measuring the nanoscale thermal conductivity (Fiege et al, 1999;Ju, 1999;Huxtable et al, 2002).…”
Section: A-sthm In 3ω Variantmentioning
confidence: 98%
“…In most A-SThM systems, the tip is heated by a high-density current flowing through it. This additional feature does not affect the P-SThM-like temperature measurement; therefore, two variants of A-SThM are available (Wielgoszewski et al, 2011a): While operating the first of these, the amount of heat dissipated by the tip is constant. In the latter, it is modulated so that the temperature of the tip is constant.…”
Section: A-sthmmentioning
confidence: 99%
“…The measurements were taken in passive mode (P-SThM), which means that the thermal nanoprobe was used as a resistive temperature sensor; it was connected to a modified Wheatstone bridge, driven from a current source, so that the probe current was basically constant throughout a single experiment and in the range of 25-50 A within the experiments described in this paper (see also Wielgoszewski et al, 2011b;Wielgoszewski and Gotszalk, 2015). The tip temperature T tip was determined according to tip calibration based on melting points of reference materials, described by Wielgoszewski et al (2014).…”
Section: Afm-based Experimentsmentioning
confidence: 99%
“…The microscope was equipped with a home-made SThM module, an analog power and resistance (P/R) meter for direct recording of the probe resistance Z pr signal (Wielgoszewski et al, 2011b(Wielgoszewski et al, , 2014) and a combined analog precision voltage follower-and-inverter to provide buffered bipolar operation of KPFM bias.…”
Section: Afm-based Experimentsmentioning
confidence: 99%